2014
DOI: 10.5539/jedp.v4n1p238
|View full text |Cite
|
Sign up to set email alerts
|

Familial and Economic Influences on the Gender-Related Educational and Occupational Aspirations of Rural Adolescents

Abstract: Economic, occupational, and social shifts in rural economies have influenced nuanced changes in the educational and occupational aspirations of rural adolescent women and men. However, there is limited contemporary research that examines the aspirations of rural adolescents at the beginning of the 21st century. Drawing on a sample of 8,756 rural adolescents in the United States, we examine how familial, geographic, and economic variables influence gender-related differences in educational and occupational aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…Parents tend to socialize their children in an attempt to realize their own expectations, and thus, socialization goals are shaped by parents' personal beliefs and attitudes (Darling & Steinberg, 1993;Grusec & Goodnow, 1994). Consistent with this proposition, a notable body of research has indicated that parental career expectations, defined as parental attitudes and hopes for children's future occupational achievements, are associated with adolescents' career developmental outcomes, including career explorations, concerns, and indecisions (Leung, Hou, Gati, & Li, 2011;Meece, Askew, Agger, Hutchins, & Byun, 2014;Sawitri, Creed, & Zimmer-Gembeck, 2014;. In general, parents with higher (yet not extremely high) levels of career expectations tend to be more motivated and involved in providing children with career-related resources, guidance, and support to promote children's career aspirations, planning, explorations, and actions (Meece et al, 2014;Sawitri et al, 2014;.…”
Section: Career-related Parental Processes and Adolescents' Career Dementioning
confidence: 96%
See 2 more Smart Citations
“…Parents tend to socialize their children in an attempt to realize their own expectations, and thus, socialization goals are shaped by parents' personal beliefs and attitudes (Darling & Steinberg, 1993;Grusec & Goodnow, 1994). Consistent with this proposition, a notable body of research has indicated that parental career expectations, defined as parental attitudes and hopes for children's future occupational achievements, are associated with adolescents' career developmental outcomes, including career explorations, concerns, and indecisions (Leung, Hou, Gati, & Li, 2011;Meece, Askew, Agger, Hutchins, & Byun, 2014;Sawitri, Creed, & Zimmer-Gembeck, 2014;. In general, parents with higher (yet not extremely high) levels of career expectations tend to be more motivated and involved in providing children with career-related resources, guidance, and support to promote children's career aspirations, planning, explorations, and actions (Meece et al, 2014;Sawitri et al, 2014;.…”
Section: Career-related Parental Processes and Adolescents' Career Dementioning
confidence: 96%
“…To our knowledge, studies in this field have predominantly used variable‐centered approaches in analyses and examined the unique associations between different parental processes and child career developmental outcomes at the average level (i.e., examining the associations among variables at the entire sample level rather than further classify the entire sample into subgroups ) (e.g., Kanten et al., ; Leung et al., ; Li & Kerpelman, ; Meece et al., ; Sawitri et al., ; Sawitri et al., ; Sawitri et al., ). Although a number of important findings have been obtained from prior research, some questions cannot be addressed by utilizing variable‐centered approaches.…”
Section: Career‐related Parental Processes and Adolescents’ Career Dementioning
confidence: 99%
See 1 more Smart Citation
“…Rural youth live in areas high in social capital with strong shared values and connections between families, schools, and religious institutions (Byun, Meece, Irvin, & Hutchins, 2012c;Elder & Conger, 2000). These connections are critical in shaping educational and residential aspirations for adulthood (Byun et al, 2012c;Elder & Conger, 2000;Johnson et al, 2005;Meece et al, 2014;Petrin, Farmer, Meece, & Byun, 2011).…”
Section: Recent Socioeconomic Transformations In Rural Communitiesmentioning
confidence: 99%
“…We used a recent national survey of rural high school students, and paid particular focus to (a) gender differences in expected transition times, and (b) how the educational aspirations of rural men and women shape their transition times into adulthood. We focused on gender because it plays a key role in understanding the future expectancies of adulthood among young adults in rural areas (Blackwell & McLaughlin, 1999;Crockett & Beal, 2012;Crockett, Shanahan, & Jackson-Newsom, 2000;Meece, Askew, Agger, Hutchins, & Byun, 2014). Women today hold increasingly significant roles in the Strange, 2009;Lichter & Brown, 2011).…”
Section: Introductionmentioning
confidence: 99%